Law on Coastal Zone Planning in Vietnam - Nguyen Tien, Dat (VNU Journal of Science: Legal Studies; Vol 42 No 1, 2026)
Vietnam recognizes the importance of developing a "sea-oriented" economy and has early embarked on constructing a legal framework for governing marine spaces. The coastal zone represents area of dynamic economic activity, contributing a significant part of the national economy. The Vietnam Integrated Coastal Zone Management Strategy, with a vision to 2030, together with numerous policies and guidelines on coastal planning, has been approved. However,  their effectiveness and the degree of coordination among these instruments remain insufficiently clear, requiring continued reform and improvement in the coming period.